2018
DOI: 10.1111/aos.13913
|View full text |Cite
|
Sign up to set email alerts
|

Topical cyclosporine‐A versus prednisolone for herpetic stromal keratitis: a randomized controlled trial

Abstract: Purpose: To compare topical cyclosporine-A 2% eye drop (Cs-A) with prednisolone acetate 1% eye drop for treatment of herpetic stromal keratitis (HSK). Methods: In this randomized clinical trial, 38 eyes of 33 patients with HSK were randomly assigned to receive either 2% Cs-A or 1% prednisolone acetate eye drops. All subjects received oral acyclovir 400 mg twice a day. Slit-lamp examination, Scheimpflug tomography corneal optical densitometry (Pentacamâ, Oculus Inc., Wetzlar, Germany), best-corrected visual acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The findings of these other investigations are similar to those of our own. In comparison with our study, Peyman et al [14] study revealed that CSA has same effect of prednisolone acetate 1% but can be used more in cases that have contraindication for using steroid therapy. This is different than our study as CSA Group has better clearance of stromal haze but in longer duration but Group B has shorter duration of healing but with more complications especially recurrence of the disease.…”
Section: Discussionsupporting
confidence: 64%
“…The findings of these other investigations are similar to those of our own. In comparison with our study, Peyman et al [14] study revealed that CSA has same effect of prednisolone acetate 1% but can be used more in cases that have contraindication for using steroid therapy. This is different than our study as CSA Group has better clearance of stromal haze but in longer duration but Group B has shorter duration of healing but with more complications especially recurrence of the disease.…”
Section: Discussionsupporting
confidence: 64%
“…The first, central, zone covers the annulus over a 2-mm diameter zone, the second covers the 2–6-mm diameter zone, the third covers the 6–10-mm diameter zone, and the last covers the annulus over a 10–12-mm diameter zone. 1618…”
Section: Methodsmentioning
confidence: 99%
“…The first, central, zone covers the annulus over a 2-mm diameter zone, the second covers the 2-6-mm diameter zone, the third covers the 6-10-mm diameter zone, and the last covers the annulus over a 10-12-mm diameter zone. [16][17][18] All patients had a complete preoperative eye examination, including BCDVA, slit-lamp biomicroscopy, and fundus examination. In addition, Goldman applanation tonometry (GAT) was done before and at each postoperative visit.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Resistance to acyclovir occurs due to extended use[ 171 ], and mutation in the viral thymidylate kinase and DNA polymerase which decreases enzyme affinity for its substrate[ 172 - 174 ]. Topical cyclosporine drops and prednisolone acetate drops are statistically similar in potency for stemming inflammation and preventing scar development[ 175 ].…”
Section: Antiviral Therapy For Herpes Simplex Keratitis: Efficacy And...mentioning
confidence: 99%